Management of canine leishmaniosis in endemic SW European regions: a questionnaire-based multinational survey - Bourdeau, Patrick (BioMed Central, 2014)
BACKGROUND: Canine leishmaniosis (CanL) caused by Leishmania infantum is a widespread endemic disease in SW Europe. This study was designed to determine how veterinarians clinically manage CanL in this region by analysing information collected in a questionnaire completed by local veterinarians working in clinics in France, Portugal, Greece, Spain, Italy and Slovenia. METHODS: Over the period 2004–2011, a questionnaire on CanL was sent to 12,546 small animal clinics located in the six countries surveyed. The questionnaire with 10 items comprising open and closed questions sought to obtain comparable data regarding the main clinical manifestations of CanL, the diagnostic methods used, the treatment regimens selected, recommended preventive measures and awareness of the important public health implications of CanL. RESULTS: The data collected reflect similarities in the clinical manifestations reported although there was some variation in the concurrent diseases described, and wide variation in the clinical management of CanL among the countries examined in terms of dosing regimens, therapeutic agents and the criteria used to diagnose CanL. Most veterinarians properly informed dog owners about the preventive measures available and about the zoonotic implications of CanL. CONCLUSIONS: This survey describes the current situation in SW endemic countries in Europe regarding the clinical management of CanL. The data collected reveal a need to unify criteria from evidence-based medicine to determine and similarly apply the best diagnostic and treatment methods available for this disease in the different countries.